Update on Nanoparticle-Based Drug Delivery System for Anti-inflammatory Treatment - Wang, Huailan; Zhou, Yunxiang; Sun, Qunan; Zhou, Chenghao; Hu, Shiyao; Lenahan, Cameron; Xu, Weilin; Deng, Yongchuan; Li, Gonghui; Tao, Sifeng (Frontiers in Bioengineering and Biotechnology, 2021)
Nanobiotechnology plays an important role in drug delivery, and various kinds of nanoparticles have demonstrated new properties, which may provide opportunities in clinical treatment. Nanoparticle-mediated drug delivery systems have been used in anti-inflammatory therapies. Diseases, such as inflammatory bowel disease, rheumatoid arthritis, and osteoarthritis have been widely impacted by the pathogenesis of inflammation. Efficient delivery of anti-inflammatory drugs can reduce medical dosage and improve therapeutic effect. In this review, we discuss nanoparticles with potential anti-inflammatory activity, and we present a future perspective regarding the application of nanomedicine in inflammatory diseases.